Psychological factors associated with body weight status among overweight and obese children in Kedah, Malaysia - Abdul Karim, Wan Mohd Nurussabah (2021)
Childhood obesity was a growing global phenomenon. In Malaysia, 29.8% children and adolescents aged between five to seventeen, were OW or obese (National Health and Morbidity Survey, 2019). Obesity was a multifactorial disorder, associated with biological, environmental and psychological factors which were the prominent variables that plays roles in its pathogenesis. Many studies have been conducted in Malaysia to identify the causes of the childhood obesity. However, there was lack of studies that based on psychological, beliefs or perceived factors that caused the obesity among children. Thus, the crosssectional study was carried out to determine the association of socio demographic factors, psychological factors towards weight reduction and body weight status (BWS) among overweight (OW) and obese children in Kedah, Malaysia. The list of OW and obese children from standard 4 and 5 were provided by respective school teachers taken from the National Physical Fitness Standard (SEGAK) test. A total of 398 children aged 10 to 11 years participated in this study, consisting of 221 boys and 117 girls. The proportion of children recruited from the urban and rural school was 61.6% and 38.4% respectively. Based on body mass index (BMI) classification, 24% of participants were identified as OW and 76% obese. Majority of participants (64.6%) were classified under B40 category where 70% of their parents had at least secondary education. The children were measured for weight, height, waist circumference, hip circumference. They also required to complete the self-administered questionnaire in group guided by researcher, covering socio-demographic profiles and psychological factors of perceived body image, perceived benefits of weight reduction, perceived barriers to weight reduction, perceived self efficacy in dietary practice and exercise. The body image perception was adapted from ‘The seven male and female child figure rating scale’ and the psychological factors scale instrument from the Health Belief Model (HBM). Overall, 5.8% of the respondents perceived their BWS as underweight and 41% of obese respondents perceived they were not in the obese category. As for socio-demographic factors showed that school locality and father’s education level were associated with BMI (x2 = 8.49, p = 0.004, x2 = 6.61, p = 0.037), WC (x2 = 11.05, p = 0.001, x2 = 10.04, p = 0.007) and WHtR (x2 = 4.97, p = 0.026, x2 = 15.31, p < 0.001). Meanwhile, psychology factors such as self-efficacy in exercise (BMI: x2 = 8.768, p = 0.012) and perceived BWS (BMI: x2 = 15.71, p < 0.001) showed association with children BWS. The study also revealed that household income (x2 = 15.70, p < 0.001), parent’s education level (mother: x2 = 11.59, p = 0.003, father: x2 = 12.14, p = 0.002) and parent’s occupation level (mother: x2 = 19.36, p < 0.001, father: x2 = 9.97, p = 0.041) were associated with school locality. Children perceived self-efficacy in exercise was significantly higher in boys (t = 3.202, p = 0.001) and among urban (t = - 0.423, p = 0.001) school children. In addition, there was no significant difference between body image and sex. Logistic regression analysis reported that sex was moderately associated with obesity (BMI) and AO (WHtR), where girls were less likely to be obese than boys and children where the fathers had secondary education level were less likely (BMI (aOR) 0.34: 95% Cl 0.10, 1.16) to be obese or AO compared to father with tertiary education level. There were associations between perceived self efficacy in exercise, perceived BWS and BMI. For WC classification, the association was found between perceived BWS and WC (p = 0.02, aOR 0.54: 95% Cl (0.32,0.91). The results of multiple linear regression analysis showed perceived benefits of weight reduction (BMI: F (3, 394) = 30.89, p = 0.01), perceived body image (BMI: F (2, 395) = 42.36, p < 0.001), (WC: F (2, 395) = 31.03, p < 0.001), (WHtR: F (2, 395) = 4.93, p = 0.008) as well as body size discrepancy score (BMI : F (1, 396) = 39.33, p < 0.001), (WC: F (1, 396) = 39.98, p < 0.001), (WHtR: F (1, 396) = 5.66, p = 0.018) and perceived self-efficacy in exercise (WC: F (3, 394) = 25.58, p < 0.001) were the strongest psychological factors contributor towards children BWS. Meanwhile, household income and household size were the most sociodemographic factors contributor towards children BWS. There was association between psychological factor with children BWS (BMI, WC and WHtR). However, from the study, either one of the classifications was recommended to be used to avoid confusion of main contributing factor. Which BWS classifications is more accurate was not studied. According to the literature review, the most widely used measure of weight status is BMI. BMI as dependent variable to ease the comparison between countries. However, alternative health screening methods such as WHtR showed their privilege which easier to conduct and can apply for all ages, sex and locality. Further studies were needed to confirm these findings among the OW and obese children. Effort to design health promotion programs to achieve ideal BWS for OW and obese children should be taken integrating with identified factors.